Pengaruh Karakteristik UKM pada Kapabilitas Inovasi dan Kinerja Inovasi UKM (Studi Kasus pada Sentra IKM Alas Kaki Jawa Timur) - Esti Dwi Rinawiyanti; Benny Lianto (Universitas Bunda Mulia, 2017)
Footwear industries get the priority in East Java Province because of their big contribution to the economy and labor absorption. In order to survive and to achieve the competitive advantage they need to do innovation. The innovation capabilities can be measured through Technological Innovation Capabilities (TIC), while the innovation performance can be assessed with Technological Innovation Performance (TIP). This research was conducted to identify SMEs characteristics (scale, age, and product type) and to analyze whether there were different impacts of those characteristics on TIC and TIP. Data collection was completed through questionnaire distribution to 192 footwear SMEs in three footwear center in East Java (Surabaya, Sidoarjo, and Mojokerto). The grand mean of each dimension of TIC and TIP was obtained by calculating the results of questionnaire which used Likert scale. The grand mean can be as a description of TIC and TIP level in those three areas. For TIC, the majority footwear SMEs were on the medium and high level. The highest level of TIC was achieved by footwear SMEs in Mojokerto (4.09), Surabaya got a medium (3.18), and Sidoarjo obtained the lowest (2.81). For TIP, the majority of footwear SMEs had the medium and low level. Footwear SMEs in Sidoarjo held the highest level (3.05), then the footwear SMEs in Mojokerto (2.86), and the lowest is footwear SMEs in Surabaya (2.05). Based on the MANOVA analysis it can be recognized that almost all characteristics of footwear SMEs (scale, age, product type) gave no significant impacts on TIC and TIP. Except among footwear SMEs in Surabaya the age of SMEs had an effect on TIC and TIP.Keywords: Footwear SMEs, Innovation Capabilities, Innovation Performance